PENGEMBANGAN MODUL TEKNIK GAMBAR MANUFAKTUR KELAS XI TP SMK TKM TEKNIK PURWOREJO - Murwanto; suparmin; setuju setuju (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine the feasibility of the Manufacturing Image Engineering Module which can be used as teaching material in Class XI TP at the Purworejo Technical TKM Vocational School. This research uses a type of Research and Development to validate and develop products. The Development Model used in this study includes: 1) searching for potentials and problems, 2) gathering information, 3) product design, 4) design validation, 5) design revisions, 6) product testing, 7) product revisions, 8) usage tests , 9) product revisions, 10) mass product / product dissemination . Data analysis uses three tests, namely material experts, media experts, field tests and reliability tests. The results showed that the Manufacturing Engineering Technique module was declared feasible as a Class XI TP teaching material at the Purworejo Technical TKM Vocational School. This is based on the results of the following analysis: (1) Based on the aspects of self- intruction, self contained aspects, stand alone aspects, adaptive aspects and user friendly aspects, the average total score was 3.20 so that it was included in the